Quality of life and its associates in narcolepsy 1 and 2 types and idiopathic hypersomnia - Galušková, K; Nevšímalová, S; Příhodová, I; Dostálová, S; Mazouchová, A; Šonka, K (Sleep medicine, 2025)
OBJECTIVE AND BACKGROUND: Health-related quality of life (HRQoL) is reduced in narcolepsy type 1 (NT1), but proper information on HRQoL in narcolepsy type 2 (NT2) and idiopathic hypersomnia (IH) is lacking. This study examines HRQoL of NT1, NT2, IH, and healthy controls (HC) and assesses the HRQoL associates in these diseases. PATIENTS AND METHODS: 117 adults (64 NT1, 22 NT2, 31 IH; 61.5 % women; 38.3 ± 12.0 years; 71.8 % treated) and 41 HC (53.7 % women; 35.9 ± 9.6 years) completed questionnaires assessing sleepiness, fatigue, symptoms severity, sleep inertia, depressive and anxiety symptoms, HRQoL, and underwent a semi-structured interview. Data were analyzed using the Mann-Whitney and Kruskal-Wallis tests, Spearman's correlation coefficient, and regression analysis. RESULTS: HRQoL of NT1, NT2, and IH, separately, was poorer compared to HC (p < 0.001). According to the 36-Item Short Form Health Survey, the mental HRQoL was more impaired in NT2 and IH than NT1 (p < 0.05) in association with more pronounced depressive symptoms (p < 0.01; p < 0.05, respectively) and sleep inertia (p < 0.01; p < 0.01, respectively). Psychiatric disorders were more prevalent in NT2 and IH versus NT1 (p < 0.05). CONCLUSION: HRQoL is reduced in NT1, NT2, and IH, with this reduction being more pronounced in NT2 and IH. Poor mental HRQoL of NT2 and IH was associated both with the severity of depressive symptoms and more intense sleep inertia.
Keywords: Surveys and Questionnaires; Humans; lidé středního věku; úzkost; Quality of Life; Female; Narcolepsy; dospělí; lidé; narkolepsie; Fatigue; kvalita života; Anxiety; průzkumy a dotazníky; Adult; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Idiopathic Hypersomnia; idiopatická hypersomnie; únava; Severity of Illness Index; Depression; mužské pohlaví; deprese